"ATTITUDES TOWARD ENTREPRENEURSHIP DURING THE SOVIET ERA AND ITS REFLECTION IN PROSE WORKS" - Farida A. Toshboyeva (Western European Studies, 2026)
The article analyzes the image of an industrialist, factory owner, and entrepreneur reflected in Russian and Uzbek fiction. It proves that this image has negative features and forms negative stereotypes. These include, for example, the understanding of the world of business people as a “dark kingdom”. Industrialists and factory owners are depicted in connection with moral decline. The author, citing examples, proves that Russian literature contributed to the formation of a social stereotype that it is impossible to earn big money in an honest way.
Keywords: image of an entrepreneur; Russian literature; Uzbek literature